2008
DOI: 10.1089/omi.2008.0001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Oxidative Stress and Inflammation Related Genes in Peripheral Blood Mononuclear Cells in Response to a Low-Calorie Diet: A Nutrigenomics Study

Abstract: Nutrigenomics is a new application of omics technologies in nutritional science. Nutrigenomics aims to identify molecular markers of diet-related diseases and mechanisms of interindividual variability in response to food. The aim of this study was to evaluate peripheral blood mononuclear cells (PBMC) as a model system and readily available source of RNA to discern gene expression signatures in relation to personalized therapy of obesity. PBMC were collected from obese men before and after an 8-week low-calorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 53 publications
3
93
0
1
Order By: Relevance
“…GAPDH was used as internal control for efficiency of RT-PCR and subsequent normalization. The results were calculated by the 2 ÀDDCt method [11].…”
Section: Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
“…GAPDH was used as internal control for efficiency of RT-PCR and subsequent normalization. The results were calculated by the 2 ÀDDCt method [11].…”
Section: Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
“…The use of these cells in nutrition-related studies is increasing due to the number of different studies performed in both animals and humans that have demonstrated the relationship of PBMCs-captured metabolic changes with the fasting and feeding cycles (Bouwens et al 2007;Caimari et al 2010a, b;Oliver et al 2013) and with the intake of specific nutrients or bioactive food compounds such as fatty acids, proteins, carbohydrates and polyphenols (van Erk et al 2006;Crujeiras et al 2008;Bouwens et al 2009;Konstantinidou et al 2009;Khymenets et al 2009;Bouwens et al 2010;Camargo et al 2010;Rudkowska et al 2011;Van Dijk et al 2012a, b;Tomé-Carneiro et al 2013;van der Velpen et al 2013; Electronic supplementary material The online version of this article (doi:10.1007/s12263-014-0438-y) contains supplementary material, which is available to authorized users. Afman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…CR in these nonhuman primates has a number of positive metabolic, hormonal, and neural benefits (Ramsey et al 2000;Colman et al 2009), some of which are inter-related, including via the diverse actions of insulin and improved glucoregulation (Willette et al 2012b). Based on previous cell culture and blood analyses from these monkeys (Kim et al 1997;Willette et al 2010) and the demonstration that CR reduces IL-8 gene expression in humans (Crujeiras et al 2008), we predicted that CR would: (1) lower blood IL-8 levels and (2) increase blood IL-10 levels. Further, we anticipated this CR-induced shift in cytokine activity would be statistically associated with volume and microstructural density in the hippocampus and several other brain regions.…”
Section: Introductionmentioning
confidence: 99%